2021
DOI: 10.1080/21655979.2021.1960462
|View full text |Cite
|
Sign up to set email alerts
|

Circ_nuclear factor I X (circNfix) attenuates pressure overload-induced cardiac hypertrophy via regulating miR-145-5p/ATF3 axis

Abstract: Cardiac hypertrophy can cause heart failure. However, the mechanisms underlying the progression of cardiac hypertrophy remain unclear. Emerging evidence suggests that circular RNAs (circRNAs) play a critical role in cardiac hypertrophy. However, the association between circ_nuclear factor I X (circNfix) and cardiac hypertrophy remain largely unknown. Therefore, the aim of the present study was to explore the role of circNfix in cardiac hypertrophy. In order to detect the function of circNfix in cardiac hypertr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 57 publications
0
28
0
Order By: Relevance
“…The blood vessel and the needle were ligated together, and then the needle was removed to achieve the corresponding degree of blood vessel constriction. After the ligation was completed, sutures were sequentially completed [ 23 ]. After the arterial arch ligation, once the mouse has spontaneous breathing and a strong response to the pinch, the tracheal intubation was pulled out, and the mouse was placed in a cage containing autoclaved bedding, feed, and drinking water.…”
Section: Methodsmentioning
confidence: 99%
“…The blood vessel and the needle were ligated together, and then the needle was removed to achieve the corresponding degree of blood vessel constriction. After the ligation was completed, sutures were sequentially completed [ 23 ]. After the arterial arch ligation, once the mouse has spontaneous breathing and a strong response to the pinch, the tracheal intubation was pulled out, and the mouse was placed in a cage containing autoclaved bedding, feed, and drinking water.…”
Section: Methodsmentioning
confidence: 99%
“…Recent work showed that miR-145-5p worsens pathological response in AngII-treated cardiomyocytes, by decreasing the expression of activating transcription factor 3 (ATF3). ATF3 is part of the cAMP response element-binding protein/ATF family, and its expression has shown protective effects in hypertensive hearts [ 41 , 42 ]. In this study, inhibition of this miRNA showed restoration of ATF3 levels and consequent attenuation of pressure overload-induced hypertrophy [ 41 ].…”
Section: Ncrnas In Pressure-overload-induced Cardiac Hypertrophymentioning
confidence: 99%
“…ATF3 is part of the cAMP response element-binding protein/ATF family, and its expression has shown protective effects in hypertensive hearts [ 41 , 42 ]. In this study, inhibition of this miRNA showed restoration of ATF3 levels and consequent attenuation of pressure overload-induced hypertrophy [ 41 ]. Interestingly, circ_nuclear factor I X (circNfix), reportedly, sponged miR-145-5p and abolished its detrimental effect on inhibiting ATF3 expression.…”
Section: Ncrnas In Pressure-overload-induced Cardiac Hypertrophymentioning
confidence: 99%
See 1 more Smart Citation
“…MicroRNAs have drawn more and more attention in cardiovascular research field [ 6 , 7 ]. Indeed, mounting evidence shows that this 21~25 nt long oligonucleotide are critically involved in regulation of a series of biological processes in cardiovascular system, such as physiological and/or pathological cardiac hypertrophy, cell apoptosis, autophagy, cardiac inflammatory response, and remodeling [ 8–14 ].…”
Section: Introductionmentioning
confidence: 99%